Bioelectrochemical Stimulation of Electromethanogenesis at a Seawater-Based Subsurface Aquifer in a Natural Gas Field - Ishii, Shun'ichi; Imachi, Hiroyuki; Kawano, Kenjiro; Murai, Daisuke; Ogawara, Miyuki; Uemastu, Katsuyuki; Nealson, Kenneth H.; Inagaki, Fumio (Frontiers in Energy Research, 2019)
In subsurface anoxic environments, microbial communities generally produce methane as an end-product to consume organic compounds. This metabolic function is a source of biogenic methane in coastal natural gas aquifers, submarine mud volcanoes and methane hydrates. Within the methanogenic communities, hydrogenotrophic methanogens and syntrophic bacteria are converting volatile fatty acids to methane syntrophically via interspecies hydrogen transfer. Recently, direct interspecies electron transfer (DIET) between fermentative/syntrophic bacteria and electrotrophic methanogens has been proposed as an effective interspecies metabolite transfer process to enhance methane production. In this study, in order to stimulate the DIET-associated methanogenic process at deep biosphere-aquifer systems in a natural gas field, we operated a bioelectrochemical system (BES) to apply voltage between an anode and a cathode. Two single-chamber BESs were filled with seawater-based formation water collected from an onshore natural gas well, repeatedly amended with acetate, and operated with 600 mV between electrodes for 21 months, resulting in a successful conversion of acetate to methane via electrical current consumption. One reactor yielded a stable current by 200 mA/m2 with a coulombic efficiency (CE) of >90%; however, the other reactor, which had been incidentally disconnected for 3 days, showed less electromethanogenic activity with a CE of only 10%. The 16S rRNA gene-based community analyses showed that two methanogenic archaeal families, Methanocalculaceae and Methanobacteriaceae, were abundant in cathode biofilms that were mainly covered by single-cell-layered biofilm, implicating them as key players in the electromethanogenesis. In contrast, family Methanosaetaceae was abundant at both electrodes and the electrolyte suspension only in the reactor with less electromethanogenesis, suggesting this family was not involved in electromethanogenesis and only activated after the no electron flow event. On anodes covered by thick biofilms with filamentous networks, family Desulfuromonadaceae dominated in the early stage of the operation, while family Geobacteraceae (mainly genus Geoalkalibacter) increased their frequencies during the longer-term operation, which indicates that these families were correlated with electrode-respiring reactions. These results indicate that the BES reactors with voltage application effectively activated a subsurface DIET-related methanogenic microbiome in the natural gas field, and specific electrogenic bacteria and electromethanogenic archaea were identified within the anode and/or cathode biofilms.